Discovery of a novel polymer for human pluripotent stem cell expansion and multilineage differentiation - Celiz, Adam D.; Smith, James G.W.; Patel, Asha K.; Hook, Andrew L.; Rajamohan, Divya; George, Vinoj T.; Flatt, Luke; Patel, Minal J.; Epa, Vidana C.; Singh, Taranjit; Langer, Robert; Anderson, Daniel G.; et al. (Wiley, 2015)
A scalable and cost-effective synthetic polymer substrate that supports robust expansion and subsequent multilineage differentiation of human pluripotent stem cells (hPSCs) with defined commercial media is presented. This substrate can be applied to common cultureware and used off-the-shelf after long-term storage. Expansion and differentiation of hPSCs are performed entirely on the polymeric surface, enabling the clinical potential of hPSC-derived cells to be realized.